The International Legal Issue of Attribution of Conduct to a State – The Case Law of the International Courts and Tribunals - Stryjkowska, Sylwia (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
The article aims to broaden the subject of the attribution of conduct to a State by pre-senting different grounds for attributing State responsibility. It surveys main the prin-ciples of attribution, which were affirmed in international judicial decisions and specifies circumstances which extend beyond the general rule under which States incur responsi-bility only for the conduct of its organs. The provisions of the Articles on the Responsi-bility of States for Internationally Wrongful Acts constitute a primary point of reference of the research and are followed by examples of their practical application.